2023
DOI: 10.3390/ijms241814399
|View full text |Cite
|
Sign up to set email alerts
|

Scopolamine-Induced Memory Impairment in Mice: Effects of PEA-OXA on Memory Retrieval and Hippocampal LTP

Carmela Belardo,
Serena Boccella,
Michela Perrone
et al.

Abstract: Transient global amnesia, both persistent and transient, is a very common neuropsychiatric syndrome. Among animal models for amnesia and testing new drugs, the scopolamine test is the most widely used for transient global amnesia (TGA). This study examined the scopolamine-induced deficits in working memory, discriminative memory, anxiety, and motor activity in the presence of intranasal PEA-OXA, a dual antagonist of presynaptic α2 and H3 receptors. Male C57BL/6 mice were treated with intraperitoneal scopolamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Consistently, electrophysiological analysis has shown LTP recovery in the dentate gyrus of the hippocampus. Therefore, this study has confirmed the neuroprotective and pro-cognitive activity of PEA-OXA (probably through an increase in the extracellular levels of biogenic amines) in improving transient memory disorders, for which the available pharmacological tools are obsolete or inadequate and are not directed on specific pathophysiological targets [41].…”
supporting
confidence: 68%
See 1 more Smart Citation
“…Consistently, electrophysiological analysis has shown LTP recovery in the dentate gyrus of the hippocampus. Therefore, this study has confirmed the neuroprotective and pro-cognitive activity of PEA-OXA (probably through an increase in the extracellular levels of biogenic amines) in improving transient memory disorders, for which the available pharmacological tools are obsolete or inadequate and are not directed on specific pathophysiological targets [41].…”
supporting
confidence: 68%
“…Moreover, the domain of behavioral or neuropsychiatric symptoms has been found to be less investigated, thus prompting new prospective studies with homogeneous design [38] since the latter affect some 99% of patients over the course of the disease [39] and they are managed with potentially harmful antipsychotics [40]. Belardo et al [41] have attempted a preclinical approach to the development of novel non-pharmacological control of AD and associated neuropsychiatric symptoms. They investigated transient and persistent global amnesia which is a very common neuropsychiatric syndrome.…”
mentioning
confidence: 99%